Production of M-Size Neon Tetra Fish Paracheriodon innesi in Recirculation System with Density of 25, 50, 75 and 100 litre-1 - Budiardi, T.; Solehudin, M.A.; Wahjuningrum, D. (Indonesian Society of Scientific Aquaculture (ISSA), 2008)
Quality and quantity of freshwater were important factors in aquaculture. The farmers of neon tetra fish (Paracheriodon innesi) usually rear them in aquarium with simple methods, so that gave low productivity. Increasing density could be increased the production and its continuity and also more efficient in land and water. Rearing of neon tetra with density of 25, 50, 75 and 100 litre-1 in recirculation system were no influence for fish body length, growth of body length and coefficient of variants (p>0,05). But those densities of fish rearing affected survival rate, end density and profit (p0,05), namun berpengaruh nyata terhadap kelangsungan hidup, kepadatan akhir dan keuntungan (p